Where does the garbage go? - Showers, Paul.; Chewning, Randy (New York : HarperCollins, 1994)
Discusses the growing garbage and trash problem in the United States and its possible solutions.
3.1
K-3
Keywords: Recycling (Waste, etc.) -- Juvenile literature; Refuse and refuse disposal -- Juvenile literature; Recycling (Waste); Refuse and refuse disposal; Recycling; Refuse and refuse disposal